Plasma cell proliferation in monoclonal gammopathies: measurement using BU-1 antibody in flow cytometry and microscopy: comparison with serum thymidine kinase. Issue 5 (May 1995) - Schambeck, C M; Wick, M; Bartl, R; Lamerz, R; Fateh-Moghadam, A
Abstract : AIMS–The labelling index as defined by the percentage of bone marrow plasma cells doubling their DNA in the S phase is a useful prognostic factor in multiple myeloma. The aim of this study was to examine the specificity and sensitivity of a new flow cytometric method for measuring the labelling index. METHODS–Bone marrow specimens from five patients with monoclonal gammopathy of undetermined significance and 61 patients with multiple myeloma were investigated. The labelling index (LI%) was determined by means of a microscopic and flow cytometric method using the antibromodeoxyuridine antibody BU-1. Serum thymidine kinase, another index of proliferation, was measured by radioimmunoassay. RESULTS–Good comparability (r = 0.83) and nearly equal imprecision (CV < 20%) were found with microscopic and flow cytometric methods of LI% measurement. However, 1000 or more cells had to be counted by microscopy around the cutoff value to avoid an unacceptable imprecision. Plasma cells with increased S phase (LI% > 1%) were characterised by their reduced light chain fluorescence intensity ratio between plasma cells and nonspecifically stained cells (7.9 v 14.8, p < 0.002), that is, by their generally lowered cytoplasmic immunoglobulin content. There was a moderate correlation between thymidine kinase and labelling index (r = 0.56, p < 0.001). At 100% specificity, myelomas with proliferating plasma cells were more sensitively detected by the labelling index than by serum thymidine kinase (55% v 32% sensitivity). CONCLUSIONS–The labelling index represents a more specific and sensitive proliferation marker than serum thymidine kinase. Flow cytometry does not result in greater precision.